The Role of Vitamin C in the Treatment of Depression - Reza Bidaki; Mahsa Mahdavi Firoozabadi; Mahsa Motamed; Sina Taherzadeh Borujeni; Azadeh Nadjarzadeh (Journal of Nutrition and Food Security, 2023)
some studies have suggested that vitamin C deficiency may play a role in the etiology of depression although the efficient dose and time of prescription is not clear now.  Also, it is not known which antidepressant drugs could be more efficient in augmentation with vitamins. Nowadays, due to the importance and more prevalence of psychiatric disorders, dietary supplements which would augment the effects of drugs have been taken into consideration. Moreover, dose titration of anti-depressant drugs is a lifelong challenge due to unwanted side effects